Deciphering the pharmacological effects of andrographolide on erythrocytes and Plasmodium falciparum 3D7 via metabolic changes by the ¹H NMR-based metabolomics approach - Alapid, Ashraf Ahmad Issa (2021)
Malaria is a serious health problem associated with high morbidity and mortality rates, affecting millions of people across the world. The evolution of drug resistance among various strains of Plasmodium falciparum has thwarted the control efforts, thereby prompting scientists to seek for new and effective alternative therapeutic agents in order to forestall the menace caused by the parasite. This study was undertaken to evaluate and elucidate the pharmacological effects of andrographolide (AG) on P. falciparum 3D7 and erythrocytes using 1H-NMR-based metabolomics approach. The first part of the study was aimed at investigating the anti-plasmodium effect of AG against P. falciparum 3D7, its time-dependent effect as well as its impact on the cellular morphology of various stages of plasmodium intra-erythrocytic cycle as compared to the conventional drug chloroquine (CQ). The malaria drug sensitivity assay was carried out using pLDH and Giemsa-stained thin blood smears to determine the differences and the morphological changes at different time intervals during the growth stages of the parasite. In the second part of this study, the IC50 and time-dependent of AG and CQ were used to determine the pharmacological effects of AG and CQ on the metabolic change of uninfected erythrocytes (uRBCs), infected erythrocytes (iRBCs) and the P. falciparum 3D7 parasite in vitro. The 1H NMR-based metabolomics approach using Principal Component Analysis (PCA) and Orthogonal Partial Least Square discriminant analysis (OPLS-DA) were used. Overall, the results reveal that AG showed a good growth inhibitory effect (IC50 =4.14μM) that was substantially lower than that of CQ (IC50 =20.19 nM). Unlike CQ, which showed its utmost activity within the first 12 hours of the cycle, the AG effect was more prominent during the second 12 hours interval of the cycle (early trophozoites stage). Although AG failed to produce any effect on the morphology of the ring stage, it produced a noticeable change in the morphological appearance and the sizes of the mature trophozoites after 12 hours. In contrast, the rings and trophozoites stage of the parasites were fairly affected in the chloroquinetreated flasks within the first 12 hours and 24 hours of the cycle, respectively. Based on unsupervised data analysis PCA, the effects of AG and CQ on the metabolic changes of uRBCs showed a clear separation between all uRBCs samples with a total variance of 89.10%. A total of 28 and 32 metabolites were identified as biomarkers in uRBCs-AG and uRBCs-CQ, respectively. In uRBCs-AG, ten metabolic pathways were determined as disturbed metabolic pathways, including riboflavin metabolic pathway, D-Glutamine and D-glutamate metabolism, phenylalanine metabolism, arginine and proline metabolism, glutathione metabolism, arginine biosynthesis, citrate cycle, pyruvate metabolism, alanine, aspartate and glutamate metabolism and glycolysis/gluconeogenesis. In contrast, in uRBCs-CQ, nine metabolic pathways have been determined as disturbed metabolic pathways similar to uRBCs-AG except for glutathione metabolism. These findings suggest an evident relationship between AG and CQ associated with metabolic perturbations in uRBCs. The effects of AG and CQ on the metabolic changes of iRBCs, the PCA and OPLS-DA showed ideal differentiation between iRBCs samples treated and untreated. Thirty-five blood metabolites were identified from the 1H-NMR spectra analysis of iRBCs samples. The outcome of PCA showed clear discrimination between AG and CQ. Both PC1 and PC2 show a total variance of 77.10%. A total of 23 and 24 metabolites were identified as biomarkers in iRBCs-AG and iRBCs-CQ, respectively. The metabolic pathways analysis revealed ten metabolic pathways were identified as disturbed in all groups. The iRBCs untreated group had a high number of disturbed metabolic pathways, including alanine, aspartate and glutamate metabolism, glutathione metabolism, arginine and proline metabolism, and riboflavin metabolism. In the group of iRBCs-CQ, the disturbed metabolic pathways identified as alanine, aspartate and glutamate metabolism, arginine and proline metabolism, and glutathione metabolism. Whereas in the iRBCs-AG, the disturbed metabolic pathways identified include glyoxylate and dicarboxylate metabolism, glycine, serine and threonine metabolism, and histidine metabolism. The effects of AG and CQ on the metabolic changes of P. falciparum 3D7 in-vitro were identified. The results of multivariate data analysis show a clear discriminant between P. falciparum 3D7 samples treated and untreated. The model showed a total variance of 89.9% described by the PC1 and PC2. A total of 19 and 21 metabolites were identified as biomarkers in groups of P. falciparum 3D7-AG and P. falciparum 3D7- CQ, respectively. In P. falciparum 3D7-AG, very few metabolites biomarkers were observed, including threonine, ornithine, riboflavin, lactate and glutathione, compared to the group treated with CQ, which showed a high number of biomarkers. Analysis of the metabolic pathways reveals two metabolic pathways were significantly disturbed in P. falciparum 3D7-AG group; arginine and proline metabolism, and glutathione metabolism. In P. falciparum 3D7-CQ group, six disturbed metabolic pathways were identified: glyoxylate and dicarboxylate metabolism, glutathione metabolism, alanine, aspartate and glutamate metabolism, arginine biosynthesis, purine metabolism and citrate cycle. In conclusion, the present study is the first to report on the antimalarial activity of AG utilizing the 1H NMR-based metabolomics approach. Results from this study suggest that the disturbed metabolic pathways identified could well serve as drug targets for future development of andrographolide-based therapeutic agents against P. falciparum 3D7.